“I don’t watch that anymore”: an analysis of online comments by German soccer fans on their relationship to their favored clubs - Kaden, Martin; Brandt, Christian; Bauers, Sebastian Björn; Bunar, Jonathan; Hovemann, Gregor (Frontiers in Psychology, 2023)
Introduction Soccer fans are important stakeholders of their favored clubs; yet, although there is manifold literature on this subject, there are still open questions concerning supporters’ relationship and loyalty to those clubs, such as potential fan exits, where supporters turn away from their preferred team. Existing literature describes diverging evidence as to whether an exit is possible and whether fans’ loyalty prevents that response. Against this background, it is important to examine how the relationship between fans and soccer clubs presents itself from the fans’ perspective. This study focuses on German soccer fans because an increasing number of media reports note problems for the fans in this regard, reporting eroded loyalty, increasing alienation, or turning away. Methods By means of a qualitative and explorative approach (thematic analysis), this study analyzes online fan comments associated with the mentioned reports. A purposive sample of 17 media reports with 10,902 associated comments written/published between 2020 and 2023 was included in this study. Results The thematic analysis show that fans reflect their relationship to favored clubs in three ways: negative changes in the emotional relationship, negative behavioral changes in the relationship, and no or positive changes in the relationship. A wide continuum of negative emotional and behavioral changes is identified, ranging from a deterioration of the inner bond with the favored club to different levels of ceasing soccer-related consumption. As explanations for the (potential) dynamics and changes in the relationship, fans reflect a broad and diverse field of developments in the context of German soccer. The differentiated developments are systemized within four categories: commercialization, governance, attractiveness, and the COVID-19 pandemic. Discussion The results are discussed and contextualized referring to the Exit-Voice-Loyalty-Framework and thematically relevant literature. Particularly far-reaching is the finding that there are indeed fans in the field of soccer who are capable of permanently abandoning (exiting) formerly supported clubs. The article concludes with theoretical and managerial implications emerging from the results, as well as limitations and areas of interest for further research.